X Y
-2 11
-1 7
0 3
1 -1
2 -5
-2 = 16 times minus 2 plus 4y equals to 12
-1 = 16 times minus 1 plus 4y equals to12
0 = 16 times 0 plus 4y equals to 12
1 = 16 times 1 plus 4y equals to 12
2 = 16 times 2 plus 4y equals to 12
Therefore,
-2 = 16 * -2 + 4y = 12
-32 + 4y = 12
4y = 12 + 32
4y = 44
y = 44/4
y = 11
-1 = 16 * -1 + 4y = 12
-16 + 4y = 12
4y = 12 + 16
4y = 28
y = 28/4
y = 7
0 = 16 * 0 + 4y = 12
0 + 4y = 12
4y = 12 + 0
4y = 12
y = 12/4
y = 3
1 = 16 * 1 + 4y = 12
16 + 4y = 12
4y = 12 - 16
4y = -4
y = -4/4
y = -1
2 = 16 * 2 + 4y = 12
32 + 4y = 12
4y = 12 - 32
4y = -20
y = -20/4
y = -5